Access time to pasture has an effect on goats’ milk production and body condition - Fança B.; Pommaret A.; Lefrileux Y.; Damez-Marti R. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Increasing the proportion of grass in rations, without decreasing the total intake, is nowadays a key aspect of goat feeding. The objective is thereby to maintain or even improve individual performance, keep goats in good metabolic health and ensure an efficient utilization of forage resources. Various studies focusing on daily access times to pasture have been conducted between 2015 and 2018 in two experimental stations, including the ‘Station du Pradel’ in the South East of France (Ardèche, 07). The experiment reported here lasted 49 days, during spring 2018. The objective was to compare a continuous access to pasture of 7h vs 10h per day. The animals were separated in homogeneous groups of 59 goats (46 multiparous and 13 primiparous) and were milked once a day. Access time had significant effect on milk production and bodyweight. Goats that were grazed outdoors for 10h produced 260g more milk (+8%) and lost only 2.8kg during the experimental period, vs 4.0kg for the 7h-group. This can be explained by a difference in the time spent ingesting grass at pasture: 5h30 for the 7h-group, vs 6h15 for the 10h-group (method Lifecorder). The proportion of time spent ingesting grass was higher for the 7h-group (73.7% of the time outside) than for the 10h-group (60.5%). Also, primiparous goats spent more time (+10%, whatever the group) ingesting grass than multiparous goats. These results are slightly different from those obtained in western France.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)